Correlation Between Visceral Fat And Lipid Profile in Myocardial Infarction Patients - Yuniari, Dwi; Puruhita, Niken; Probosari, Enny; Subagyo, Hertanto Wahyu; Nugrohowati, Annta Kern (Medica Hospitalia : Journal of Clinical Medicine, 2023)
BACKGROUND : Previous studies reported that visceral fat plays an important role in cardiovascular disease, even in non-obese individuals. Bioelectrical impedance analysis (BIA) is a non-invasive and radiation-free method for assessing visceral fat. Not much is known whether visceral fat correlates with lipid profile in myocardial infarction (MI) patients in Indonesian population. PURPOSE : To analyze the correlation between visceral fat and serum lipid profile in MI patients. METHODE : This is a correlational study on 32 MI patients hospitalized at the ICCU of RSUP Dr. Kariadi Hospital recruited with consecutive sampling. Visceral fat was measured by BIA SECA mBCA 525 series, data regarding levels of total cholesterol, triglycerides, low density lipoprotein (LDL), and high density lipoprotein (HDL) were gathered from medical record. The data were normally distributed, then the hypothesis was tested with the Pearson. RESULT : The mean age of the subjects was 55 ± 9.88 years, with 87.5% being male. As many as 81.3% of subjects experienced ST-elevation myocardial infarction (STEMI). The average body mass index (BMI) was 26.2 ± 3.68 kg/m², in which 40.6% of subjects were classified as grade 1 obesity. The majority of subjects (93.8%) had high visceral fat. As many as 68.8% of subjects had high LDL levels with an average of 120.5 ± 38.84 mg/dL. HDL average was 35±13.55 mg/dL with 62.5% of subjects having low HDL levels. More than half of the subjects (56.3%) experienced hypertriglyceridemia with an average of 157.4 ± 55.84 mg/dL. Visceral fat was significantly related to total cholesterol and triglycerides (r=0.40; p=0.02 and r=0.36; p=0.04). CONCLUSION : There is a significant correlation between visceral fat and total cholesterol and triglycerides in MI patients.